TNF-α gene expression in relation to TNF-α level and bone mineral density in Polish patients with celiac disease - Skoracka, Kinga; Hryhorowicz, Szymon; Michalak, Michał; Kaczmarek-Ryś, Marta; Dziechciowska, Iga; Dobrowolska, Agnieszka; Krela-Kaźmierczak, Iwona (Frontiers in Endocrinology, 2025)
BackgroundOsteopenia and osteoporosis are common complications of celiac disease (CD).ObjectivesGiven the inflammatory background of bone disorders, this study aimed to assess the impact of TNF-α gene expression and its serum level on bone mineral density (BMD) in individuals with CD.Patients and methodsThe study at the start included 70 adults: 51 women and 9 men with CD, and 10 healthy controls: 8 women, 2 men. In the first phase of the study, densitometric measurements of the lumbar spine (L1–L4) and femoral neck (FN) were performed using dual-energy x-ray absorptiometry (DXA) to identify patients with celiac disease and decreased BMD. These patients constituted Group A (CD with osteopenia/osteoporosis, n = 12). Group B (CD with normal BMD, n = 6), and Group C (healthy controls with normal BMD, n = 6) were matched for sex, age and body mass to patients in group A. In the second phase of the study, TNF-α gene expression was quantified using the real-time quantitative PCR (qRT-PCR) method, and serum TNF-α levels were measured with an enzyme-linked immunosorbent assay (ELISA). In third phase, statistical analyses were conducted to investigate the correlations between TNF-α expression and serum TNF-α levels with bone and anthropometric parameters.ResultsNo statistically significant differences in TNF-α gene expression or TNF-α serum levels were found between the groups. In Group A, TNF-α expression did not correlate with bone or anthropometric measures. However, in Group B, lower TNF-α expression correlated with higher BMI, FN BMD, L1–L4 BMD, and Z-scores. In contrast, healthy controls showed a positive correlation between TNF-α expression and BMD, T-score, and Z-score of the FN. There was also no statistically significant correlation between TNF-α cytokine concentration, and the parameters studied in groups A and B.ConclusionsIn this study, TNF-α, both in terms of gene expression and serum level, does not appear to correlate with BMD status in individuals with CD and osteopenia/osteoporosis. Larger longitudinal studies integrating additional cytokines and signaling pathways are needed to clarify the role of TNF-α in bone loss in celiac disease.